(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is examined the role of local government in the formation of civil society. The author puts forward the view that the problems of organization and functioning of local government in the formation of civil society in Kazakhstan is closely intertwined with national issues of political, social, economic, spiritual and cultural development.